Development of Porous Silicon(Si) Anode Through Magnesiothermic Reduction of Mesoporous Silica(SiO2) Aerogel for All-Solid-State Lithium-Ion Batteries - Pratik S. Kapadnis; Kangsanin Kim; Kisun Nam; Yongseon Kim; Hyung-Ho Park; Haejin Hwang (Gels)
All-solid-state lithium-ion batteries (ASSLBs) are attractive energy storage devices because of their excellent gravimetric and volumetric capacity and ability to supply high power rates. Porous silicon (Si) is a promising material for an anode in lithium-ion batteries due to its high capacity and low discharge potential. However, Si anodes cause significant problems due to strong volume growth during the lithiation and delithiation processes, which results in rapid capacity fading and poor cycle stability. To overcome this problem, we developed mesoporous silica (SiO2) aerogels into porous silicon (Si) anodes using a magnesiothermic reduction (MTR) process. By effectively preserving the porous structure, this approach enables the material to endure volume fluctuations while maintaining its structural integrity during cycling. In our study, we demonstrated a feasible approach to fabricate the porous silicon (Si) from hydrophobic and hydrophilic silica (SiO2) aerogel and magnesium powder (Mg) through the MTR process at 600~900 °C. The sample obtained after the reduction process was treated with hydrochloric acid (HCl) to remove byproducts. As prepared, Si was characterized using various techniques, including XRD, XRF, FT-IR, XPS, SEM, and BET, which confirmed the successful production, chemical purity, and structural retention of Si. Furthermore, the coin cell was fabricated using Si as an anode, and the electrochemical performance was analyzed. The charge/discharge cycling tests at 1 C and 0.02~2 V (vs. the Li condition) revealed the effects of silicon content, wettability, and interfacial compatibility on electrode performance. Conversely, for better understanding, a long-term cycling test was conducted at 1 C rate, 0–1.5 V (vs. Li) to evaluate capacity retention. Our findings highlight the potential application of silicon (Si) aerogels produced from silica (SiO2) aerogels by magnesiothermic reduction to improve lithium-ion battery performance.